Mouth rinsing and ingesting a bitter solution improves sprint cycling performance - Gam, S.; Guelfi, K. J.; Fournier, P. A. (Medicine & Science in Sports & Exercise, 2014)
Purpose: There is evidence that carbohydrate (CHO) mouth rinsing can improve endurance exercise performance as well as muscle force production and sprint performance. Whether the oral administration of non-CHO tastants also affects exercise performance is not known. The purpose of this study was to investigate whether mouth rinsing and ingesting a bitter-tasting solution of quinine improves maximal sprint cycling performance.